Analysis of Electrode Temperature Influence on EOS Parameters - Sinkevičius, V.; Šumskienė, L.; Virbalis, J. A. (Elektronika ir Elektrotechnika, 2006)
Instability of cut–off voltage is the one of the main reasons of kinescope reject. After the analysis of kinescopes, rejected for cut–off voltage instability, we made the conclusions: first, not the exterior, but interior distances have to be measured during the assembly of EOS, to avoid the influence of deviations from thicknesses of electrodes and the second, that to equalize the cut-off voltages in the multiple beam EOS, cathodes have to be fixed with deviation not worse than ±1 μm in respect of the calculated positions. They can be adequately calculated only if thermal deformations during the operation of EOS are taken in to account. Ill. 12, bibl. 5 (in English; summaries in English, Russian and Lithuanian).